The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/pharmaceutics14010184
|View full text |Cite|
|
Sign up to set email alerts
|

Simulating the Hydrodynamic Conditions of the Human Ascending Colon: A Digital Twin of the Dynamic Colon Model

Abstract: The performance of solid oral dosage forms targeting the colon is typically evaluated using standardised pharmacopeial dissolution apparatuses. However, these fail to replicate colonic hydrodynamics. This study develops a digital twin of the Dynamic Colon Model; a physiologically representative in vitro model of the human proximal colon. Magnetic resonance imaging of the Dynamic Colon Model verified that the digital twin robustly replicated flow patterns under different physiological conditions (media viscosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
(96 reference statements)
1
6
0
Order By: Relevance
“…However, the stimulated colon may generate hydrodynamic conditions that lie somewhere between 25 and 50 rpm. This data builds upon previous conclusions that the use of > 50 rpm in the USPII is not recommended for colon-targeted dosage forms [ 10 ].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…However, the stimulated colon may generate hydrodynamic conditions that lie somewhere between 25 and 50 rpm. This data builds upon previous conclusions that the use of > 50 rpm in the USPII is not recommended for colon-targeted dosage forms [ 10 ].…”
Section: Resultssupporting
confidence: 84%
“…Higher release was achieved in the USPII at 25, 50 and 100 rpm. Although conclusions cannot be drawn on the shear rates likely to have occurred from this comparison, since a constant shear is applied in the USPII and shear in the DCM has a high spatiotemporal dependence [ 10 ]. Previous MRI studies of the DCM found velocities to vary from −2.16–0.78 cm s −1 and shear rate fluctuating between 0–8 s −1 when slower CPPWs were applied (0.4 and 0.8 cm s −1 ) at the same volume and viscosity as in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 The Blue Brain Project, for example, began in 2005 as a collaboration between EPFL (Ecole Polytechnique Fédérale de Lausanne) and International Business Machines and aims to model the neocortical column. 23 Schütt et al 24 developed a DT of the Dynamic Colon Model that considered media viscosity, and peristaltic wave speed. It provided new insights for dissolution testing beyond established pharmacopoeial methods.…”
Section: Resultsmentioning
confidence: 99%
“…In the original publication [ 1 ], there was a mistake in Figure 6 when published. The experimental data points in the upper diagram were missing.…”
mentioning
confidence: 99%